Analysis of business opportunities of secondary use of spectrum: The case of TV white space for mobile broadband access - Jan Markendahl; Östen Mäkitalo (International Telecommunications Society (ITS), 2011)
The introduction of mobile broadband technology, smartphones and dongles has resulted in a tremendous increase of mobile data traffic. Future demand for more capacity can be met by allocation of more bandwidth and new spectrum bands to mobile communication. But spectrum is a scarce resource and allocation of new licensed bands will only partly satisfy the growing demand. Another possibility is secondary use of spectrum bands which primarily have been allocated for other services, e.g. TV or weather and traffic control radars. The secondary use exploits un-used spectrum in frequency, time or physical location. Such un-used spectrum in the TV bands is called TV white space (TV WS). In this paper we will focus on the business analysis of cellular use of TV white spaces where the service is mobile broadband access. A number of business cases are analyzed where we look into mobile broadband services in rural and urban areas and for indoor use. The service can be provided by a mobile network operator with licensed spectrum or by an operator using TV white spaces only. The analysis indicates that market entrants will be in a more difficult position than the established actors. New operators need to invest in networks, platforms, marketing and customers. Promising business cases are presented for existing mobile operators that use TV WS as complement for capacity expansion in urban areas and for local operators (e.g. facility owners) that will use TV WS and own indoor infrastructure in order to offer indoor capacity to mobile operators.
Keywords: L96; L50; O13; 330; Mobile broadband networks; spectrum allocation; cost structure analysis; spectrum; business case network deployment strategies; telecommunications; economic development of natural resources; regulation and industrial policy